Analysis of Observed Temperature Changes in The Northern Region of Sri Lanka Based on Climate Change Perspective - Piratheeparajah, N. (Universiti Sains Malaysia, 2022)
Temperature is the primary weather element that determines the other weather element in a place. The Northern region of Sri Lanka has different climatic conditions that clearly define summer and winter because of its geographical setup. The area is categorized under the dry zone because of its climatic condition. However, the Northern region has unique characteristics compared with the other areas of the dry zone. This study aims to identify the changes in the temperature pattern of Northern Sri Lanka based on monthly, seasonal, and annual temperature data. The data were obtained from various sources, such as the meteorology department, the Department of Irrigation of Northern Province, and the Economic Development Department. The Mann Kendal (MK) trend and Sen's slope estimator analysis were employed to study the temperature data. According to the MK analysis, there is a positive trend in the annual temperature pattern in all six stations, such as Thirunelvely, Iranaimadu, Murungan, Akkarayankulam Vavuniya, and Kanukkerny, and Sen's values of these stations show the increase in temperature in the study area. The minimum and maximum temperature of the annual pattern indicate a significant increase of 0.35°C & 0.63°C, respectively, in the study area. Further compared to the 1930 to 1960 climatic period, the current climatic period (1990 to 2020) has a 0.84°C increase in the study area. The results show that the average temperature of every climatic period increases in the study area. Additionally, there are increases in the study area's monthly temperature pattern, especially in July, which significantly increases by 0.47°C in the study area. An appropriate mitigation and adaptation action would help the sustainable development of the Northern region of Sri Lanka.
Keywords: Climate change; Temperature; Northern Province; Sri Lanka; Global Warming